UNVEILING VIRTUE: A CHARACTER VALUE ANALYSIS OF THE KHATAM QUR'AN TRADITION - Asmiah; Erlisnawati; Hendri Marhadi; Mitha Dwi Anggriani (Universitas Majalengka, 2025)
The tradition of completing the Qur'an is one of the traditional ceremonies carried out as a form of gratitude and appreciation for children who have been able to read the Qur'an and complete it. In the tradition of completing the Qur'an, there are many character values ​​that can be taken and used as a medium for character education in schools. This study aims to determine the character values ​​contained in the tradition of completing the Qur'an. The research method used is a descriptive qualitative method, which was carried out at SDN 14 Pekanbaru. The research subjects consisted of 1 principal, 1 Islamic Religious Education teacher, and 6 grade VI students who had participated in this tradition. Data collection techniques were observation, in-depth interviews, and documentation. The results of this study indicate that the tradition of completing the Qur'an has several stages of activity, namely preparation activities, consisting of meetings to determine the schedule and place and preparation of equipment. Furthermore, the implementation activities consist of a parade, reading the Qur'an by students, and wearing samir and giving certificates. Finally, the closing activity consists of reading prayers and cleaning the activity environment. The activity of completing the Qur'an can bring out several characters, namely religious character, cooperative character, hard-working character, democratic character, independent character, creative character, responsible character, mutual respect character, tolerance character, and environmental care character. This study can be concluded that the tradition of completing the Qur'an has several characters that can be used as a reinforcement of character education in elementary school students.